2014
DOI: 10.1364/oe.22.000411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structurally sensitive loss in GaN-based VCSEL cavities and its effect on modal discrimination

Abstract: Lateral loss causes optical energy to leave the laser cavity in the transverse, lateral, direction, and is sometimes neglected to simplify the numerical simulations. However, in contrast to outcoupling and absorption losses, we show that the lateral loss can change drastically with only nanometer-sized changes of the cavity structure, from being virtually zero to becoming the major source of cavity loss, since the cavity becomes antiguiding. This can be explained as the opening of a channel of efficient resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Buried tunnel junctions have also been demonstrated to laterally confine the current 130 , and if the introduced structural step from the overgrown TJ transfers into the top DBR, it might also provide simultaneous optical guiding 132,133 .…”
Section: ωCmmentioning
confidence: 99%
See 3 more Smart Citations
“…Buried tunnel junctions have also been demonstrated to laterally confine the current 130 , and if the introduced structural step from the overgrown TJ transfers into the top DBR, it might also provide simultaneous optical guiding 132,133 .…”
Section: ωCmmentioning
confidence: 99%
“…However, to achieve an efficient device with low threshold it is important to ensure a good lateral overlap between the optical mode and the carriers in the QWs. In fact, it has been shown that most apertures used for current confinement result in optically anti-guided structures with associated high losses 132,133 , for more details see Section 4. Switching to index-guided structures instead, will contribute to lowering threshold currents and can be an effective way to reduce filamentation, something often seen in GaN-VCSELs 27,28,30,32,39,40,46 , and also seen in early proton-implanted gain-guided GaAs-VCSELs 135,136 .…”
Section: ωCmmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, electrically pumped polariton emitters and conventional VCSELs have been demonstrated in III-nitride based MCs at room temperature (RT). However, the pside designs including indium-tin-oxide (ITO) transparent conducting layer (TCL) and dielectric materials based current aperture in the reported devices induce a negative guiding effect and lateral optical loss [13][14][15]. To provide a sufficient positive guiding effect, Cheng et al utilized an intra-cavity low-index AlN layer to serve as a lateral optical/current aperture and achieved a high-quality-factor (Q) emission; however, no lasing action was observed in their MC light emitter due to the lack of TCL [16].…”
Section: Introductionmentioning
confidence: 99%